Perceptions of Social Mobility and Political Trust in China: The Mediating Role of Perceived Fairness - Lu, Haiyang; Zeng, Keya; Yang, Long (Social justice research, 2024)
Based on nationally representative data from the 2019 and 2021 Chinese Social Survey, this study examined the relationship between perceptions of upward and downward social mobility (PUSM/PDSM) and political trust by using the diagonal reference model and ordinary least squares model. We found that PUSM was positively related to political trust, while PDSM was negatively related to it after excluding the influence of social positions of origin and destination. We also provided evidence that perceived fairness mediated the nexus between PUSM/PDSM and political trust. Our findings underscored the pivotal role of perceived social mobility in shaping the political trust of Chinese citizens and elucidate the micro-level psychological mechanisms underlying this relationship. Hence, we advocate for the implementation of policies geared towards fostering upward mobility and alleviating inequality, aimed at addressing potential crises in political trust. Considering the decline in overall social mobility and the exacerbation of inequality following the COVID-19 epidemic, this research holds heightened contemporary significance.